The Relationship of Neoadjuvant Taxanes, Anthracyclines, Cyclophosphamide Chemotherapy on Nutritional Status Based on Body Mass Index (BMI) and Albumin Measurements in Locally Advanced Stage Breast Cancer Patients in Bahteramas Hospital Kendari - S Limba, Afirah Khairunnisa; Royani, Ida; Muchsin, Achmad Harun; Kamaluddin, Irna Diyana Kartika; Irsandy, Febie (http://dharmais.co.id/, 2024)
Background: Breast cancer is a disease caused by cancer cells in breast tissue. The most frequently found is locally advanced. The locally advanced stage refers to stages IIIA, IIIB, and IIIC. Neoadjuvant is the treatment for locally advanced. The Taxane, Anthracycline, and Cyclophosphamide (TAC) is a neoadjuvant chemotherapy regimen that can cause nausea and vomiting resulting in decreased appetite and lack of nutritional intake in patients. This study aims to determine the relationship between neoadjuvant TAC chemotherapy and nutritional status based on measurements of BMI and albumin in breast cancer patients at Bahteramas Kendari Hospital.Method: This study was conducted with a retrospective cross-sectional design. The sampling technique was consecutive sampling using 41 medical records of breast cancer patients from the years 2023 to 2024 in Bahteramas Kendari Hospital.Result: There were significant changes in the nutritional status of patients who received neoadjuvant TAC chemotherapy. Before chemotherapy, the patient’s BMI was found to be in the normal category of 34.1% and decreased to 31.7% after chemotherapy. Likewise, patients with obesity were 34.1% before chemotherapy and changed to 19.5% after chemotherapy. Furthermore, there were significant changes in the patient’s albumin levels. Before chemotherapy, 38 patients had normal albumin levels (92.7%), whereas after chemotherapy only 24 patients had normal albumin levels (58.5%).Conclusion: There was a relationship between TAC neoadjuvant chemotherapy and nutritional status based on BMI and Albumin measurements before and after chemotherapy in patients with locally advanced breast cancer.